Pemberian Fitobiotik Tepung Ziziphus Mauritiana Pada Pakan Terhadap Persentase Karkas dan Lemak Abdominal Itik Hibrida - Irfan H. Djunaidi; Alvin Fahrilian Affandi (Journal of Agriprecision & Social Impact, 2024)
The research was aimed to investigate the effect of addition phytobiotics in basal feed to live weight, carcass weight, carcass percentage, and abdominal fat percentage of hybrid ducks. Hybrid duck used for research were 192 duck. The method used in this research was field experimental with Completely Randomized Design (CRD) using 4 treatments and 6 replications, there were basal feed + 0% phytobiotics (T0); basal feed + 0.20% phytobiotics (T1); basal feed + 0.25% phytobiotics (T2) and basal feed + 0.30% phytobiotics (T3). The variables measured were the percentage of carcasses and abdominal fat. The research data were analyzed using variance using the Completely Randomized Design and continued with Duncan's multiple range test if there were real differences or very real differences . The result showed that the addition of phytobiotics in basal feed to the live weight, carcass weight, carcass percentage, and abdominal fat percentage of hybrid ducks of adding leaf flour in hybrid duck feed had no significant effect (P>0.05) on body weight before slaughtering, carcass percentage of thigh and wing parts and abdominal fat. but had a significant effect (P<0.05) on carcass weight and a very significant effect (P<0.01) on the percentage of carcass breast.